Enhancing EFL Teaching in Indonesian Islamic Senior High Schools Through Artificial Intelligence Integration - Harintama, Fitrana; Muslimin, Afif Ikhwanul (Schemata: Jurnal Pascasarjana UIN Mataram, 2024)
This research aims to explore the integration of Artificial Intelligence (AI) in English as a Foreign Language (EFL) teaching within Indonesian Islamic Senior High Schools. Employing a Systematic Literature Review (SLR) methodology, the study synthesizes existing research to identify effective AI applications, challenges faced by educators and students, and the broader implications for educational reform. The findings reveal that AI can significantly enhance EFL instruction through personalized learning experiences, intelligent tutoring systems, and language learning applications, which improve student engagement and language proficiency. However, challenges such as inadequate teacher training, resource limitations, and ethical concerns regarding data privacy must be addressed to ensure successful implementation. The implications of this study highlight the need for a balanced approach that combines AI integration with human interaction in teaching practices. Additionally, it underscores the importance of professional development for educators and equitable access to technology for all students. This research contributes to the growing body of literature on AI in education and provides actionable insights for policymakers and educators seeking to enhance English language teaching in Indonesia's Islamic Senior High Schools. Keywords: Artificial intelligence, EFL teaching, Indonesia, Islamic senior high schools Penelitian ini bertujuan untuk mengeksplorasi integrasi Kecerdasan Buatan (AI) dalam pengajaran Bahasa Inggris sebagai Bahasa Asing (EFL) di Sekolah Menengah Atas Islam di Indonesia. Dengan menggunakan metodologi Tinjauan Literatur Sistematis (SLR), penelitian ini mensintesis penelitian yang sudah ada untuk mengidentifikasi aplikasi AI yang efektif, tantangan yang dihadapi oleh para pendidik dan siswa, dan implikasi yang lebih luas untuk reformasi pendidikan. Temuan tersebut mengungkapkan bahwa AI dapat secara signifikan meningkatkan pengajaran EFL melalui pengalaman belajar yang dipersonalisasi, sistem bimbingan belajar yang cerdas, dan aplikasi pembelajaran bahasa, yang meningkatkan keterlibatan siswa dan kemahiran bahasa. Namun, tantangan seperti pelatihan guru yang tidak memadai, keterbatasan sumber daya, dan masalah etika terkait privasi data harus diatasi untuk memastikan implementasi yang sukses. Implikasi dari penelitian ini menyoroti perlunya pendekatan yang seimbang yang menggabungkan integrasi AI dengan interaksi manusia dalam praktik pengajaran. Selain itu, penelitian ini juga menggarisbawahi pentingnya pengembangan profesionalisme bagi para pendidik dan akses yang adil terhadap teknologi untuk semua siswa. Penelitian ini berkontribusi pada literatur yang berkembang tentang AI dalam pendidikan dan memberikan wawasan yang dapat ditindaklanjuti bagi para pembuat kebijakan dan pendidik yang ingin meningkatkan pengajaran bahasa Inggris di Sekolah Menengah Atas Islam di Indonesia. Kata kunci: Kecerdasan buatan, pengajaran bahasa Inggris, Indonesia, sekolah menengah atas Islam